1998
DOI: 10.1007/s004670050440
|View full text |Cite
|
Sign up to set email alerts
|

Calyceal microlithiasis in children: report on 196 cases

Abstract: Recognition of children at greatest risk for urolithiasis may allow early detection or prevention of stone formation. We report clinical data from 196 children aged 0.9-15.9 years in whom renal ultrasound examination revealed hyperechogenic spots in renal calyces less than 3 mm in diameter. We called this finding "calyceal microlithiasis" (CM). There was a history of urolithiasis in 70.4% of patients in at least one first- or second-degree relative. Presenting symptoms were recurrent abdominal pain, dysuria, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
27
3
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 13 publications
9
27
3
6
Order By: Relevance
“…Calyceal microlithiasis was defined by the finding of hyperechogenic spots in renal calyces. These were usually devoid of a shade cone and were ≤3 mm in diameter [15]. A single scan is not enough when it is necessary to distinguish with certainty between microcalculi and similar surrounding structures.…”
Section: Methodsmentioning
confidence: 99%
“…Calyceal microlithiasis was defined by the finding of hyperechogenic spots in renal calyces. These were usually devoid of a shade cone and were ≤3 mm in diameter [15]. A single scan is not enough when it is necessary to distinguish with certainty between microcalculi and similar surrounding structures.…”
Section: Methodsmentioning
confidence: 99%
“…In 1998, La Manna et al [7] in their study of children with urinary symptoms, for the first time, used the term ‘renal calyceal microlithiasis' (RCM) for the echogenic shadows <3 mm in the ultrasound imaging of the urinary system. They suggested that RCM might be the first step in calculus formation [7]. Since then, there is a lot of controversy regarding the RCM and its clinical importance; some studies showed that RCM has got a benign course that does not increase the risk of stone formation.…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, La Manna et al [7] in their study of children with urinary symptoms, for the first time, used the term ‘renal calyceal microlithiasis' (RCM) for the echogenic shadows <3 mm in the ultrasound imaging of the urinary system. They suggested that RCM might be the first step in calculus formation [7].…”
Section: Introductionmentioning
confidence: 99%
“…77 Çapı 3 mm'den daha küçük olan bu lekelenmeler renal kalikseal mikrolitiyaz (RKM) olarak adlandırıl-maktadır. 78 RKM'ye daha çok karın ağrısı, İYE ve hematüri, dizüri gibi semptomu olan çocuklarda rastlanmaktadır; ancak hiçbir semptomun olmadığı çocuklar da olabilmektedir. 77,79 Hastalar, daha büyük renal taşı olan çocuk hastalara göre genellikle daha küçüktür (infantil dönem).…”
Section: Nütrisyonel Nedenlerunclassified
“…77,79 RKM'ler renal taş oluşumunun ilk basamağı olarak kabul edilmektedir ve ilerleyen yaşlarda sıklıkla renal taş oluşumu ile birliktedir. 78,80 Ancak Türkiye'den bildirilen iki çalış-mada, RKM'nin %37 hastada, diğer çalışmada ise %29 hastada zaman içerisinde kendiliğinden kaybolduğu saptanmıştır. 77,79 RKM oluşumunda daha çok metabolik anomaliler, daha az olarak da anatomik anomaliler nedendir.…”
Section: Nütrisyonel Nedenlerunclassified